Endoplasmic Reticulum Stress: A Critical Molecular Driver of Endothelial Dysfunction and Cardiovascular Disturbances Associated with Diabetes - Hatem Maamoun (14778730) (2019)
Physical inactivity and sedentary lifestyle contribute to the widespread epidemic of obesity among both adults and children leading to rising cases of diabetes. Cardiovascular disease complications associated with obesity and diabetes are closely linked to insulin resistance and its complex implications on vascular cells particularly endothelial cells. Endoplasmic reticulum (ER) stress is activated following disruption in post-translational protein folding and maturation within the ER in metabolic conditions characterized by heavy demand on protein synthesis, such as obesity and diabetes. ER stress has gained much interest as a key bridging and converging molecular link between insulin resistance, oxidative stress, and endothelial cell dysfunction and, hence, represents an interesting drug target for diabetes and its cardiovascular complications. We reviewed here the role of ER stress in endothelial cell dysfunction, the primary step in the onset of atherosclerosis and cardiovascular disease. We specifically focused on the contribution of oxidative stress, insulin resistance, endothelial cell death, and cellular inflammation caused by ER stress in endothelial cell dysfunction and the process of atherogenesis. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms20071658